Assessing the Relationship Between Green Leadership Practices and Organisational Resiliance in Sustainable HR System in Indonesia Startpup Companies - Irra Chrisyanti Dewi (Journal of Management and Bussines (JOMB), 2024)
This research aims to investigate the influence of organizational resilience and green leadership practices on sustainable human resource (HR) systems in the context of start-up businesses in Indonesia. The survey method was used to collect quantitative data from 250 respondents representing various industrial sectors. The constructs of organizational resilience, sustainable HR systems, and green leadership were tested for validity and reliability using accepted measurement models. Structural model analysis shows that organizational resilience, sustainable HR systems, and green leadership have a positive and significant relationship. In addition, mediation analysis indicates that the influence of green leadership on sustainable HR systems is partially mediated through organizational resilience. The validity of this relationship is strengthened through bootstrapping procedures. These findings provide valuable insights for organizational leaders and policy makers by illustrating the dynamics of sustainability practices in the context of start-up companies in Indonesia. The practical implications of this research emphasize the importance of building strong organizational resilience and implementing green leadership practices as a strategy to strengthen sustainable HR systems in facing future business challenges. Keywords: Green Leadership, Indonesian Business Environment, Organizational Resilience, Sustainable HR Systems, Start-Up Companies